A warrior's faith : a decorated Navy SEAL, a brutal firefight, and the belief that transformed his life /: a decorated Navy SEAL, a brutal firefight, and the belief that transformed his life. ([2015]) - Jr, Vera, Robert, 1966-
No abstract available